Chemical Characterization and Differential Lipid-Modulating Effects of Selected Plant Extracts from Côa Valley (Portugal) in a Cell Model for Liver Steatosis - Ricardo Amorim; Mário Pedro Marques; Catarina Melim; Carla Varela; Vilma A. Sardão; José Teixeira; Maria Inês Dias; Lillian Barros; Paulo J. Oliveira; Célia Cabral (Pharmaceuticals)
Background/Objectives: Côa Valley, located in the northeast of Portugal, harbors more than 500 medicinal plant species. Among them, four species stand out due to their traditional uses: Equisetum ramosissimum Desf. (hemorrhages, urethritis, hepatitis), Rumex scutatus L. subsp. induratus (Boiss. and Reut.) Malag. (inflammation, constipation), Geranium purpureum Vill., and Geranium lucidum L. (pain relief, gastric issues). Given their rich ethnomedicinal history, we evaluated their protective effects on an in vitro model of metabolic dysfunction-associated steatotic liver disease (MASLD). Methods: Decoction (D) and hydroalcoholic (EtOH80%) extracts were prepared and chemically characterized. Their safety profile and effects on lipid accumulation were assessed in palmitic acid (PA)-treated HepG2 cells using resazurin, sulforhodamine B, and Nile Red assays. Results: Chemical analysis revealed diverse phenolic compounds, particularly kaempferol derivatives in E. ramosissimum. All extracts showed minimal cytotoxicity at 25–50 µg/mL. At 100 µg/mL, only E. ramosissimum extracts maintained high cell viability. In the lipotoxicity model, E. ramosissimum decoction demonstrated the most potent effect, significantly reducing PA-induced neutral lipid accumulation in a dose-dependent manner, while other extracts showed varying degrees of activity. Conclusions: These findings highlight E. ramosissimum’s decoction, rich in kaempferol derivatives, as particularly effective in reducing lipid accumulation in this MASLD cell model while also providing a comprehensive characterization of traditionally used plants from the Côa Valley region.